2017
DOI: 10.2174/1570159x15666170504123316
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Resistant Epilepsy and Surgery

Abstract: Background:Epilepsy is a chronic brain disease that is caused by various factors and characterized by recurrent, episodic and temporary central nervous system dysfunction which results due to excessive discharge of brain neurons. In the past decades, despite the continuous development of antiepileptic drugs, there are still many patients with epilepsy progressing to drug-resistant epilepsy. Currently, surgical treatment is one of important way to cure drug-resistant epilepsy.Methods:Data were collected from We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
77
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 123 publications
(124 reference statements)
0
77
0
8
Order By: Relevance
“…In addition to the development of new drugs, there is an increasing interest in the search for new therapeutic alternatives that enable improvements in the quality of life of patients who suffer from epilepsy, particularly those in which conventional pharmacology is not effective. In these patients, surgery and deep brain stimulation might be viable treatment options 1 3 . In parallel, the research and development of new neuromodulatory tools, such as transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS), focused ultrasound or the use of static magnetic fields, are of substantial importance 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the development of new drugs, there is an increasing interest in the search for new therapeutic alternatives that enable improvements in the quality of life of patients who suffer from epilepsy, particularly those in which conventional pharmacology is not effective. In these patients, surgery and deep brain stimulation might be viable treatment options 1 3 . In parallel, the research and development of new neuromodulatory tools, such as transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS), focused ultrasound or the use of static magnetic fields, are of substantial importance 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperexcitability resulting from disruption of the balance between excitation and inhibition in nervous tissue can trigger acute seizures [ 4 ]. Imbalances cause excessive synchrony of electrical discharges from specific neurons, thus triggering a series of abnormal behaviors [ 5 ]. Inhibitory/excitatory transmission systems play a major role in such imbalances, especially the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) and the excitatory neurotransmitter glutamate [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Recent studies have shown that up to 30% of patients who suffer from epilepsy do not respond to AEDs. 4 For these patients, several alternative treatments have been utilized, including vagal nerve stimulation, deep-brain stimulation, and ketogenic diets. 5 In some cases, surgical treatment, including surgical resection, is an option for treatment of medically intractable epilepsy.…”
Section: Introductionmentioning
confidence: 99%